Aerator energy use in shrimp farming and means for improvement. Issue 1 (20th November 2020) - Boyd, Claude E.; McNevin, Aaron A.
Abstract: Estimates of aeration energy use in shrimp farming varied from 11.4 to 41.6 GJ/t shrimp (average = 19.8 GJ/t). Several opportunities for reducing energy use in aeration are available. Many farms adopt an excessive yield to installed aeration capacity ratio. Moreover, the proportion of installed aerator capacity in use and duration of aerator operation per day are often more than necessary during the initial two‐thirds of grow‐out, because adjustment is not made for the quantity of shrimp biomass. Farm‐made, long‐arm aerators used in Asia have several features leading to energy inefficiency and could be replaced by more efficient factory‐made, long‐arm aerators. Asian aquaculture aerator manufacturers should redesign aerators to include design features shown in research to improve efficiency. Dissolved oxygen concentration monitoring essential for verification of aeration performance is seldom performed by shrimp farmers. With good aeration technique, energy use for aeration should not exceed 10–15 GJ/t shrimp.